Contribution to micro- and nanoplastics hazard assessment: the lessons learnt from nanomaterials toxicity assessment - Silva, Maria João (2022)
The last decade has witness growing scientific concerns and public debate over the adverse effects that may result from marine and freshwater organisms’ exposure to plastics and microplastics. Moreover, due to microplastics degradation or direct release from domestic and industrial sources, aquatic organisms are equally exposed to nano-sized plastics (size between 1 and 100 nm, EFSA 2016). These micro- and nanoplastics have the potential to accumulate in edible tissues of the exposed organisms, including those that are part of the human diet, thus entering the human food chain (Toussaint et al., 2019). Apart from this indirect exposure route, humans are additionally exposed to tiny plastic particles through water consumption and consumer products that incorporate the so-called microbeads. In contrast to the wide range of investigation on the impact of plastics/microplastics on the ecosystem, a major question is whether micro- and nanoplastics will have a negative impact on human health. This negative impact may derive from the physicochemical nature of the micro- and nanoplastics, that resemble those of engineered nanomaterials, including their capacity to cross barriers and reach all organs and tissues, inducing deleterious effects e.g., inflammation or genotoxic effects that may lead long-term disease, such as cancer. Moreover, these plastic particles might be associated with a wide range of substances, including chemicals present in the plastic composition, e.g., metals, polychlorinated biphenyls and plasticizers or chemicals adsorbed to their surface, which may also be hazardous to human health. An effective risk assessment of micro- and nanoplastics needs to be supported by a robust hazard assessment. The experimental approach to be applied should rely on previously acquired knowledge from the toxicity assessment of different engineered nanomaterials. Indeed, the potential cytotoxic, immunotoxic and genotoxic effects of these plastic particles have to be assessed using complementary in vitro and in vivo assays and considering their specific physicochemical properties. In this work, we will present the testing strategy that has been recently applied to the genotoxicity characterization of nanomaterials in human cell models, e.g., a co-culture of human intestinal epithelial cells and mucus-producing cells, and in an integrative in vivo model (Louro et al., 2014). Particularly, the approach used to the toxicity assessment of titanium dioxide following a harmonized in vitro digestion process will be presented and its advantages and pitfalls discussed. Furthermore, the results of our previous approaches to the toxicity assessment of nanomaterials have supported the view that a thorough understanding of the relationship between the physicochemical properties, the behaviour of nanoparticles in biological systems and their mechanism of action is of utmost importance to predict their biological activity (Louro et al., 2019). Particularly, the investigation of genotoxic and epigenetic effects will be focused, given their strong association with carcinogenic effects. In summary, we propose the use of a predictive toxicology approach based on defining the key events at cellular and molecular levels, to identify and characterize the hazard of micro- and nanoplastics, reducing the in vivo experimentation to the lowest possible level.